Preparation of silver nanoparticles fabrics against multidrug-resistant bacteria. (April 2016) - Hanh, Truong Thi; Thu, Nguyen Thi; Hien, Nguyen Quoc; An, Pham Ngoc; Loan, Truong Thi Kieu; Hoa, Phan Thi
Abstract: The silver nanoparticles (AgNPs)/peco fabrics were prepared by immobilization of AgNPs on fabrics in which AgNPs were synthesized by γ-irradiation of the 10 mM AgNO3 chitosan solution at the dose of 17.6 kGy. The AgNPs size has been estimated to be about 11 nm from TEM image. The AgNPs content onto peco fabrics was of 143±6 mg/kg at the initial AgNPs concentration of 100 ppm. The AgNPs colloidal solution was characterized by UV–vis spectroscopy and TEM image. The antibacterial activity of AgNPs/peco fabrics after 60 washings against Staphylococcus aureus and Klebsiella pneumoniae was found to be over 99%. Effects of AgNPs fabics on multidrug-resistant pathogens from the clinical specimens were also tested. Highlights: AgNPs were synthesized by gamma Co-60 irradiation of Ag + /chitosan solution. AgNPs/peco fabric was prepared by deposition of AgNPs on peco fabric. AgNPs/peco fabric was tested as wrapper of patient's bed in hospital. AgNPs/peco fabric wrapper inhibited the growth of bacterial strains remarkably.